2010
DOI: 10.1108/01443581011075460
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and motor vehicle deaths in the USA: a state‐level analysis

Abstract: PurposeThe purpose of this paper is to empirically investigate the linkage between obesity and motor vehicle deaths.Design/methodology/approachThe paper specifies a model that explains highway fatalities, which accounts for obesity in its set of potential determinants. State‐level data are utilized in this paper. The values for all variables are for the year 2005. They correspond to 46 of the contiguous states for all measures. The model is estimated by multiple regressions.FindingsThe paper finds that the mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
(17 reference statements)
2
10
0
Order By: Relevance
“…There is ample evidence that obesity and alcohol consumption in combination increases the risk of developing potentially fatal liver disease (Hart et al ., ; Liu et al ., ). Moreover, in light of the results identified by Simmons and Zlatoper () and Anderson et al . (), indicating a positive association between obesity and motor vehicle fatalities, more research is needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is ample evidence that obesity and alcohol consumption in combination increases the risk of developing potentially fatal liver disease (Hart et al ., ; Liu et al ., ). Moreover, in light of the results identified by Simmons and Zlatoper () and Anderson et al . (), indicating a positive association between obesity and motor vehicle fatalities, more research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…There is ample evidence that obesity and alcohol consumption in combination increases the risk of developing potentially fatal liver disease (Hart et al, 2010;Liu et al, 2010). Moreover, in light of the results identified by Simmons and Zlatoper (2010) and Anderson et al (2012), indicating a positive association between obesity and motor vehicle fatalities, more research is needed. It is clear that the negative externality associated with drunk driving is appropriately addressed through aggressive government policy (Eisenberg, 2003;Dee et al, 2005;Grabowski and Morrisey, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jayaratne and Amal (2005) have discussed how the number and type of vehicle are associated with the number of road accidents. Walter and Thomas (2010) found that per capita income and elderly male drivers have negative associations with motor vehicle death rate in a state level analysis in the USA. Douglas et al (2016) found that GDP growth in a given year causes additional road traffic fatalities in Botswana and Zambia.…”
Section: Introductionmentioning
confidence: 99%